Introduction: Legislative innovation in exceptional times - Lohitzune Zuloaga; Lisett Páez Cuba (Oñati Socio-Legal Series)
This text introduces the thematic monograph dedicated to problematize the conceptions of normality and exceptionality in legislative production, considering the approach to social situations that also break with the considerations of what is normal or exceptional. This introduction contextualizes the eight contributions that make up this issue, divided into two blocks according to the context of action, Basque Country-Navarre or Latin America, and which analyze cases related to four major areas of exceptionality: political, health, economic and those affecting gender relations. The works gathered here share the objective of understanding the dynamics produced by the imminent need to increase the security of citizens and the consequences of legislative innovations in the different social spheres.